Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
By using a combination of lithium-containing nickel composite oxide and boron in the positive electrode active material of lithium-ion secondary batteries, the problem of high reaction resistance is solved, and higher output characteristics and cycle stability are achieved.
Patent Information
- Application Number
- CN202380075014.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-31
- Filing Date
- 2023-10-30
- Publication Date
- 2025-06-20
AI Technical Summary
The existing lithium-ion secondary batteries have high reaction resistance during use, which affects the output characteristics and cycle stability of the battery.
A positive electrode active material containing lithium nickel composite oxide has a layered structure of hexagonal crystalline and contains boron on the surface. The ratio of B and C is optimized by XPS determination to reduce the reaction resistance.
It effectively reduces the reaction resistance of lithium-ion secondary batteries, improves the output characteristics and cycle stability of the battery.
Smart Images

Figure BDA0005373671340000241 
Figure HDA0005373671350000011 
Figure HDA0005373671350000012
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a lithium ion secondary battery. Background Art
[0002] In recent years, with the popularization of portable electronic devices such as mobile phones and laptop computers, there has been a strong demand for the development of small and lightweight secondary batteries with high energy density and durability. In addition, as batteries for electric vehicles such as power tools and hybrid vehicles, there has been a strong demand for the development of high-output secondary batteries. Further, in addition to the above-mentioned required characteristics, there is a high expectation for a secondary battery that is difficult to deteriorate even after repeated use and has high durability.
[0003] As a secondary battery that meets such requirements, there is a lithium ion secondary battery. A lithium ion secondary battery is composed of a negative electrode, a positive electrode, an electrolyte, etc., and as the active materials of the negative electrode and the positive electrode, materials that can release and intercalate lithium are used. As described above, a lithium ion secondary battery has high energy density, output characteristics, and durability.
[0004] Regarding lithium ion secondary batteries, research and development are now in full swing. Among them, lithium ion secondary batteries using layered or spinel-type lithium metal composite oxides as the positive electrode material have been put into practical use as batteries with high energy density because they can obtain a high voltage of 4V class.
[0005] As the positive electrode material of a lithium ion secondary battery, lithium cobalt composite oxide (LiCoO2) that is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2) using nickel that is cheaper than cobalt, lithium nickel cobalt manganese composite oxide (LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4) using manganese, lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2), etc. have been proposed as lithium metal composite oxides.
[0006] In recent years, regarding lithium ion secondary batteries, further improvement of battery characteristics has been required. For example, research has been conducted on improvement of cycle characteristics (for example, Patent Document 1), high output, etc.
[0007]
Prior Art Documents
[0008]
Patent Documents
[0009]
Patent Document 1
[0010]
Problems to be Solved by the Invention
[0011] In recent years, there has also been a need for a positive electrode active material for a lithium ion secondary battery that can reduce the reaction resistance when used in a lithium ion secondary battery.
[0012] Therefore, in view of the problems of the above-mentioned prior art, in one aspect of the present invention, an object is to provide a positive electrode active material for a lithium ion secondary battery that can reduce the reaction resistance when used in a lithium ion secondary battery.
[0013]
Means for Solving the Problem
[0014] To solve the above problems, according to one aspect of the present invention, there is provided a positive electrode active material for a lithium ion secondary battery, containing a lithium nickel composite oxide having a hexagonal layered structure, including secondary particles formed by aggregation of a plurality of primary particles.
[0015] The lithium nickel composite oxide contains lithium (Li), nickel (Ni), titanium (Ti), boron (B), and element M (M) in the following proportions. In terms of the molar ratio, Li:Ni:Ti:B:M = a:b:c:d:e (where 0.95 ≤ a ≤ 1.10, 0.50 ≤ b < 1.00, 0.00 < c ≤ 0.05, 0.00 < d ≤ 0.03, 0.00 ≤ e ≤ 0.47, b + c + d + e = 1, and the element M is at least one element selected from the group consisting of Mn, Co, V, Mg, Mo, Ca, Cr, Zr, Ta, Nb, Na, W, Fe, Zn, Si, Sn, Cu, P, and Al).
[0016] In the XRD pattern of the positive electrode active material for the lithium ion secondary battery, the total peak intensity of the strongest lines of the titanium compound is 0.2 or less than the diffraction peak intensity of the (003) plane, which is the strongest line of the hexagonal layered structure.
[0017] When the total molar amount of lithium, nickel, titanium, boron, the element M, and carbon in the surface calculated from the XPS measurement results of the positive electrode active material for the lithium ion secondary battery is the total molar amount, and the ratio of the molar amount of carbon to the total molar amount is the C content ratio, and the ratio of the molar amount of boron to the total molar amount is the B content ratio.
[0018] The ratio of the B content ratio to the C content ratio is 0.8 or more and 30.0 or less.
[0019]
Effects of the Invention
[0020] According to one aspect of the present invention, there can be provided a positive electrode active material for a lithium ion secondary battery that can reduce the reaction resistance when used in a lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021]
Figure 1
[0022]
Figure 2A
[0023]
Figure 2B
[0024] Hereinafter, the mode for carrying out the present invention will be described with reference to the accompanying drawings. The present invention is not limited by the following embodiments, and various modifications and substitutions can be made to the following embodiments without departing from the scope of the present invention.
[0025] [Positive Electrode Active Material for Lithium Ion Secondary Battery]
[0026] The positive electrode active material for a lithium ion secondary battery in the present embodiment (hereinafter, simply referred to as "positive electrode active material") will be described below.
[0027] (1) Regarding Lithium Nickel Composite Oxide
[0028] The positive electrode active material of the present embodiment contains a lithium nickel composite oxide. The positive electrode active material of the present embodiment may be composed only of a lithium nickel composite oxide, and in this case, unavoidable impurities mixed in during the manufacturing process or the like are not excluded.
[0029] (1-1) Composition
[0030] The above-mentioned lithium nickel composite oxide may contain lithium (Li), nickel (Ni), titanium (Ti), and boron (B).
[0031] The lithium nickel composite oxide may also contain elements other than lithium, nickel, titanium, and boron. For example, it may also contain the element M described below.
[0032] The lithium nickel composite oxide preferably contains lithium (Li), nickel (Ni), titanium (Ti), boron (B), and element M (M) in the following proportions in terms of the molar ratio, Li:Ni:Ti:B:M = a:b:c:d:e.
[0033] The above a, b, c, d, and e preferably satisfy 0.95 ≤ a ≤ 1.10, 0.50 ≤ b < 1.00, 0.00 < c ≤ 0.05, 0.00 < d ≤ 0.03, 0.00 ≤ e ≤ 0.47, and b + c + d + e = 1. In addition, the element M is preferably at least one element selected from the group consisting of Mn, Co, V, Mg, Mo, Ca, Cr, Zr, Ta, Nb, Na, W, Fe, Zn, Si, Sn, Cu, P, and Al.
[0034] Lithium nickel composite oxides can be represented, for example, by the general formula: Li a Ni b Ti c B d M e O 2+α For a, b, c, d, e, and element M in the above general formula, there are already records, so the description is omitted here. α preferably satisfies, for example, -0.2 ≤ α ≤ 0.2.
[0035] (Nickel (Ni))
[0036] In lithium nickel composite oxides, the higher the nickel content ratio, the higher the capacity when used as the positive electrode material of a lithium ion secondary battery.
[0037] Therefore, as described above, b representing the nickel content ratio is preferably 0.50 or more, more preferably 0.60 or more, further preferably 0.70 or more, and particularly preferably 0.80 or more.
[0038] The upper limit value of b representing the nickel content ratio is as described above, preferably less than 1.00, and more preferably 0.97 or less.
[0039] (Titanium (Ti))
[0040] In a lithium ion secondary battery, for example, heat may be generated when a short circuit occurs between the positive electrode and the negative electrode. When the lithium ion secondary battery generates heat, the positive electrode active material is also heated. When the thermal stability of the positive electrode active material is low, it decomposes at a low temperature and releases oxygen. In addition, it is known that due to the decomposition of the positive electrode active material, the positive electrode active material, its decomposition products react with the electrolyte, further generating heat.
[0041] In this regard, by containing titanium in the lithium nickel composite oxide, the thermal stability of the positive electrode active material containing the lithium nickel composite oxide is improved. Therefore, when the lithium ion secondary battery generates heat, the decomposition of the positive electrode active material is also inhibited, and the release of the above-mentioned oxygen and further heat generation of the lithium ion secondary battery can be inhibited.
[0042] Therefore, c representing the titanium content ratio is preferably greater than 0.00, more preferably greater than 0.02, and further preferably 0.022 or more.
[0043] The upper limit value of c representing the titanium content ratio is as described above, preferably 0.05 or less, and more preferably 0.04 or less.
[0044] (Boron (B))
[0045] As described above, the lithium nickel composite oxide of the present embodiment may contain boron. According to the research of the inventors of the present invention, by containing boron in the lithium nickel composite oxide, when used in a lithium ion secondary battery, the reaction resistance can be reduced.
[0046] Although the exact mechanism for reducing the reaction resistance is not clear, it is considered that the lithium nickel composite oxide contains boron, and this boron forms a reaction product with low resistance with the lithium component attached to the particle surface of the lithium nickel composite oxide. Therefore, it is considered that on the particle surface of the lithium nickel composite oxide, the resistance reduction accompanying the insertion and extraction of lithium can reduce the reaction resistance.
[0047] As described above, d representing the content ratio of boron is preferably greater than 0.00, more preferably 0.001 or more, further preferably 0.002 or more, and particularly preferably 0.003 or more.
[0048] There is no particular limitation on the upper limit value of d representing the content ratio of boron. Considering that the effect of excessive addition will saturate, it is preferably 0.03 or less, more preferably 0.025 or less, and particularly preferably 0.02 or less.
[0049] (Element M)
[0050] As described above, in the lithium nickel composite oxide of the present embodiment, as an optional component, element M may also be contained. The element group applicable to element M has already been described, so the description is omitted here. In particular, from the viewpoint of improving the thermal stability of the lithium nickel composite oxide, for example, suppressing the thermal decomposition of the lithium nickel composite oxide, as element M, it is preferably at least one selected from cobalt (Co) and manganese (Mn).
[0051] Since element M is an optional component, e representing the content ratio of element M is as described above, preferably 0.00 or more, more preferably 0.05 or more, and further preferably 0.10 or more.
[0052] The upper limit value of e representing the content ratio of element M is as described above, preferably 0.47 or less, more preferably 0.25 or less, and further preferably 0.20 or less.
[0053] In addition, when the lithium nickel composite oxide contains multiple types of element M, the total of the content ratios of the multiple types of element M preferably satisfies the above range.
[0054] As described later, the lithium nickel composite oxide also contains carbon. However, the lithium nickel composite oxide contains carbon as an unavoidable impurity in an extremely small amount, so this carbon is not included in the general formula of the lithium nickel composite oxide, etc.
[0055] (1-2) Regarding the crystal structure
[0056] The lithium nickel composite oxide preferably has a hexagonal layered structure. By containing a hexagonal layered structure, the lithium nickel composite oxide can easily insert and extract lithium between the layers, and when used in a lithium ion secondary battery, it can particularly improve the output characteristics and cycle characteristics.
[0057] The crystal structure of the lithium nickel composite oxide can be analyzed by Rietveld refinement.
[0058] (1-3) Regarding the particle morphology
[0059] The particles of the lithium nickel composite oxide may contain secondary particles formed by aggregation of multiple primary particles.
[0060] In addition, the lithium nickel composite oxide may contain unaggregated primary particles in addition to the secondary particles. That is, the lithium nickel composite oxide may contain both primary particles and secondary particles.
[0061] (2) Boron content ratio, carbon content ratio
[0062] As described above, when the lithium nickel composite oxide contains boron and is used in a lithium ion secondary battery, the reaction resistance can be reduced.
[0063] It is considered that the boron contained in the lithium nickel composite oxide forms a reaction product with low resistance with the lithium component attached to the surface of the particles of the lithium nickel composite oxide. Therefore, it is presumed that the generation of impurities that increase the resistance, such as lithium carbonate, is suppressed on the surface of the particles of the lithium nickel composite oxide, and the reaction resistance can be reduced.
[0064] When XPS (X-ray photoelectron spectroscopy) measurement is performed on the positive electrode active material of the present embodiment, the types and amounts of elements present in the surface layer of the lithium nickel composite oxide particles contained in the positive electrode active material can be evaluated.
[0065] Then, from the viewpoint of improving the effect of reducing the above reaction resistance, when XPS measurement is performed on the positive electrode active material of the present embodiment, it is preferable that the boron (B) content ratio is high and the carbon (C) content ratio derived from lithium carbonate etc. that causes an increase in resistance is suppressed.
[0066] Here, the total amount of substances of lithium (Li), nickel (Ni), titanium (Ti), boron (B), element M, and carbon (C) in the surface calculated from the XPS measurement results of the positive electrode active material of the present embodiment is the total amount of substances, and the ratio of the amount of substance of carbon (C) to the total amount of substances is the carbon content ratio. In addition, the ratio of the amount of substance of boron (B) to the total amount of substances calculated from the XPS measurement results of the positive electrode active material of the present embodiment is the boron content ratio.
[0067] In the above case, the ratio of the boron content ratio to the carbon content ratio is preferably 0.8 or more, more preferably 1.0 or more, further preferably 2.0 or more, and particularly preferably 2.5 or more.
[0068] It can be considered that by making the ratio of the B content to the C content 0.8 or more, the proportion of components such as lithium carbonate that cause an increase in resistance is suppressed, and the proportion of compounds containing boron that contribute to low resistance is increased. Therefore, when used in a lithium-ion secondary battery, the reaction resistance can be particularly reduced.
[0069] Here, if the ratio of the B content to the C content is excessively increased, an increase in the boron content occurs in the lithium nickel composite oxide, and there is a need to suppress the contents of other nickel, titanium, and element M. In addition, in order to suppress the mixing of lithium carbonate and the like, it becomes necessary to perform precise control of the atmosphere during long-term water washing and heat treatment, which causes a decrease in battery characteristics and an increase in cost.
[0070] Therefore, the ratio of the B content to the C content is preferably 30.0 or less, more preferably 15.0 or less, still more preferably 10.0 or less, and particularly preferably 8.0 or less.
[0071] Preferably, the C content is small, for example, preferably 30% or less, more preferably 20% or less. By making the C content 30% or less, the content of compounds such as lithium carbonate that cause an increase in resistance on the surface layer of the particles of the lithium nickel composite oxide can be sufficiently suppressed. Therefore, when used in a lithium-ion secondary battery, the reaction resistance can be particularly reduced.
[0072] The lower limit value of the C content is not particularly limited, preferably 0 or more, more preferably 5% or more, still more preferably 10% or more.
[0073] The B content and the C content can be measured and calculated in the following order. First, XPS measurement is performed on the positive electrode active material. Then, semi-quantitative values are calculated from the peak areas of the spectra of lithium (Li), nickel (Ni), titanium (Ti), boron (B), element M, and carbon (C) obtained by XPS measurement, and the molar ratios of the respective components on the surface of the positive electrode active material are obtained from them. The peaks used when obtaining the molar ratios of the respective components can be selected according to elements and the like. For example, after peak separation of the measured XPS spectrum, the peak with the highest intensity can be used.
[0074] Next, using the results of the above compositional analysis, the C content, the B content, and the ratio of the B content to the C content can be calculated by the following formulas (1), (2), and (3). In the formulas, MLi, MC, MNi, MTi, MB, and MM respectively refer to the molar ratio of lithium, the molar ratio of carbon, the molar ratio of nickel, the molar ratio of titanium, the molar ratio of boron, and the molar ratio of element M calculated from the results of XPS measurement.
[0075] (C content) = [MC÷(MLi + MNi + MTi + MB + MM + MC)]×100 ··· (1)
[0076] (Proportion containing B)=[MB÷(MLi + MNi + MTi + MB + MM + MC)]×100···(2)
[0077] (Ratio of the proportion containing B to the proportion containing C)=(Proportion containing B)÷(Proportion containing C)···(3)
[0078] (3)Intensity ratio of the XRD pattern
[0079] When measuring the XRD pattern of the positive electrode active material of the present embodiment, the ratio of the sum of the peak intensities of the strongest lines of the titanium compound to the diffraction peak intensity of the (003) plane, which is the strongest line of the hexagonal layered structure (hereinafter referred to as "peak intensity ratio") is preferably 0.2 or less.
[0080] This is because when the above peak intensity ratio is 0.2 or less, almost no heterogeneous phase is formed by the titanium added to the lithium nickel composite oxide, but remains in the lithium nickel composite oxide, which can particularly improve the thermal stability.
[0081] The above peak intensity ratio is more preferably 0.1 or less.
[0082] When calculating the above peak intensity ratio, the peak intensity of the strongest line of the titanium compound can be calculated in the following order. First, identify the heterogeneous phase contained in the positive electrode active material that is not the lithium nickel composite oxide, that is, the titanium compound, through phase identification. Next, among the peaks of the determined titanium compounds, find the intensity of the peak of the strongest line with the largest intensity. Then, the peak intensities of the strongest lines of the determined titanium compounds can be added together as the sum of the peak intensities of the strongest line of the titanium compound.
[0083] Dividing the sum of the peak intensities of the strongest line of the obtained titanium compound by the diffraction peak intensity of the (003) plane, which is the strongest line of the hexagonal layered structure, can calculate the above peak intensity ratio.
[0084] (4)Regarding the titration curve
[0085] Regarding the filtrate obtained by mixing the positive electrode active material of the present embodiment with pure water and then filtering, in the titration curve obtained by neutralization titration, preferably, the volume ratio of the amount of HCl added in the region where the pH is 5.0 or more and less than 8.0 to the amount of HCl added in the region where the pH is 8.0 or more and 11.0 or less is 0.5 or less.
[0086] The filtrate used for plotting the above titration curve can be the filtrate obtained by adding 10 g of the positive electrode active material of the present embodiment to 50 mL of pure water, stirring in this pure water for 5 minutes, and then filtering to separate the solid and liquid. The pure water preferably is water that has removed as much as possible the components that affect neutralization titration, and distilled water or the like can be appropriately used. In addition, when preparing the above titration curve, as the acid for neutralization titration of the filtrate after the above filtration, that is, hydrochloric acid (HCl), 1.0 M, that is, 1.0 mol / dm 3 (1.0 mol / L) hydrochloric acid can be used.
[0087] According to the research of the inventors of the present invention, the amount of HCl added in the region where the pH in the above titration curve is 5.0 or more and less than 8.0 mainly means the HCl consumed in the reaction with lithium carbonate contained in the positive electrode active material.
[0088] In addition, when performing neutralization titration on the above filtrate of the positive electrode active material of the present embodiment, in the titration curve, in the region where the pH is 8.0 or more and 11.0 or less, compared with other pH regions, the change in pH is suppressed, and a nearly flat region appears. Specifically, for example, in the titration curve, in the region where the pH is 8.0 or more and 11.0 or less, compared with the region where the pH is 5.0 or more and less than 8.0, a region where the change in pH with respect to the amount of HCl added is small appears.
[0089] As described above, it is considered that the lithium nickel composite oxide contains a trace amount of boron, and this boron forms a lithium-boron-containing compound, which is a reaction product with low resistance, with the lithium component attached to the particle surface of the lithium nickel composite oxide. And it is considered that this lithium-boron-containing compound reduces the reaction resistance of the positive electrode active material.
[0090] It is presumed that in the above titration curve, the amount of HCl added in the region where the pH is 8.0 or more and 11.0 or less mainly means the HCl consumed in the reaction with the above lithium-boron-containing compound.
[0091] Therefore, it is considered that by making the volume ratio of the amount of HCl added in the region where the pH is 5.0 or more and less than 8.0 to the amount of HCl added in the region where the pH is 8.0 or more and 11.0 or less be 0.5 or less, suppressing the content of lithium carbonate means that the above lithium-boron-containing compound can be sufficiently generated. Therefore, it is considered that when this positive electrode active material is applied to a lithium ion secondary battery, the reaction resistance of the positive electrode active material can be particularly reduced.
[0092] The volume ratio VR of the amount of HCl added in the region where the pH is 5.0 or more and less than 8.0 to the amount of HCl added in the region where the pH is 8.0 or more and 11.0 or less can be calculated by the following formula (4).
[0093] In the following formula (4), the amount of HCl added in the region where the pH is 8.0 or higher and 11.0 or lower is denoted as "V(8.0 to 11.0)", and the amount of HCl added in the region where the pH is 5.0 or higher and less than 8.0 is denoted as "V(5.0 to 8.0)".
[0094] VR = V(5.0 to 8.0) ÷ V(8.0 to 11.0) ··· (4)
[0095] As described above, the above VR is preferably 0.5 or less, more preferably 0.25 or less, and still more preferably 0.2 or less.
[0096] The lower limit value of the above VR is not particularly limited, but since it is difficult to completely remove lithium carbonate, it is preferably 0.01 or more, more preferably 0.05 or more.
[0097] (5) Regarding the particle size distribution index and the volume average particle size
[0098] The positive electrode active material of the present embodiment is preferably such that [(D90 - D10) / volume average particle size Mv] representing the particle size distribution index is 0.70 or more and 1.20 or less, more preferably 0.80 or more and 1.00 or less.
[0099] In this specification, D10 means the cumulative 10% particle size, that is, the 10% diameter on a volume basis in the particle size distribution obtained by the laser diffraction scattering method, namely the particle size at a volume cumulative value of 10%. D90 means the cumulative 90% particle size, that is, the 90% diameter on a volume basis in the particle size distribution obtained by the laser diffraction scattering method, namely the particle size at a volume cumulative value of 90%. In other parts of this specification, D10 and D90 also have the same meaning.
[0100] The volume average particle size Mv is the average particle size weighted by the particle volume. In a collection of particles, the sum of the product of the diameter of each particle and the volume of that particle is divided by the total volume of the particles. Regarding the volume average particle size, it can be measured and calculated by the laser diffraction scattering method using a laser diffraction type particle size distribution meter.
[0101] By making the particle size distribution index of the positive electrode active material 0.70 or more, when manufacturing a positive electrode, for example, particles with a smaller particle size are arranged between particles with a larger particle size, and the packing density of the positive electrode active material can be increased.
[0102] By making the particle size distribution index of the positive electrode active material 1.20 or less, the mixing of overly large particles and tiny particles can be suppressed. When such a positive electrode active material is used in a lithium ion secondary battery, the output characteristics can be particularly improved.
[0103] The volume-average particle diameter Mv of the positive electrode active material of the present embodiment is not particularly limited, and is preferably, for example, 8 μm or more and 20 μm or less, more preferably 10 μm or more and 18 μm or less.
[0104] By making the volume-average particle diameter Mv of the positive electrode active material of the present embodiment within the above range, when the positive electrode active material of the present embodiment is used for the positive electrode of a lithium ion secondary battery, the output characteristics and battery capacity are particularly improved, and furthermore, high fillability for the positive electrode is achieved. Specifically, by making the volume-average particle diameter Mv of the positive electrode active material of the present embodiment 8 μm or more, the fillability for the positive electrode can be improved. In addition, by making the volume-average particle diameter Mv of the positive electrode active material of the present embodiment 20 μm or less, the output characteristics and battery capacity can be particularly improved.
[0105] [Manufacturing method of positive electrode active material for lithium ion secondary battery]
[0106] The manufacturing method of the positive electrode active material for a lithium ion secondary battery according to the present embodiment will be described. According to the manufacturing method of the positive electrode active material for a lithium ion secondary battery of the present embodiment, the above positive electrode active material can be manufactured. Therefore, for matters that have been described, some descriptions are omitted. In addition, the method for manufacturing the above positive electrode active material is not limited to the following manufacturing method of the positive electrode active material.
[0107] The manufacturing method of the positive electrode active material of the present embodiment may include the following mixing step, sintering step, water washing step, boron addition step, heat treatment step, and cooling step.
[0108] In the mixing step, a nickel-containing material containing elements other than lithium (Li), boron (B), and oxygen among the elements contained in the lithium nickel composite oxide, such as nickel (Ni), titanium (Ti), and an element M (M) as needed, and a lithium compound are mixed to prepare a first raw material mixture.
[0109] In the sintering step, the above first raw material mixture is sintered in an oxidizing atmosphere to form a sintered product.
[0110] In the water washing step, the sintered product obtained in the above sintering step is washed with water to obtain a water-washed powder.
[0111] In the boron addition step, the water-washed powder and a boron-containing material are mixed to prepare a second raw material mixture.
[0112] In the heat treatment step, the second raw material mixture can be heat-treated.
[0113] Each step will be described below.
[0114] (1) Mixing step
[0115] In the mixing step as described above, a nickel-containing material containing at least nickel and titanium and a lithium compound are mixed to prepare a first raw material mixture. Hereinafter, the raw materials used will be described.
[0116] (1-1) Nickel-containing material
[0117] The nickel-containing material provided to the mixing step is as described above and may contain: elements other than lithium, boron, and oxygen among the elements contained in the target lithium nickel composite oxide, namely nickel, titanium, and element M as required. In addition, in the above nickel-containing material, element M may be an optional additive component and thus may not be contained.
[0118] The nickel-containing material may contain elements corresponding to the target composition of the lithium nickel composite oxide, and its composition and the like are not particularly limited. For example, the nickel-containing material may appropriately contain a nickel composite hydroxide, a nickel composite compound which is a calcined product of the nickel composite hydroxide. In addition, the nickel-containing material may also be composed of the above nickel composite compound. Examples of the calcined product of the nickel composite hydroxide include a nickel composite oxide, and a mixture of a nickel composite oxide and a nickel composite hydroxide.
[0119] In addition, the nickel-containing material may be, for example, a material having a coating containing titanium and element M on the surface of nickel oxide, nickel hydroxide, etc., and one or more selected from the mixture of nickel oxide, nickel hydroxide, etc. and a titanium compound and a compound of element M.
[0120] When the lithium nickel composite oxide contains a plurality of element M, a mixture of a nickel composite compound containing a part of element M and a compound of the remaining element M may also be used as the nickel-containing material. In this case, the above nickel composite compound is preferably one or more selected from a nickel composite oxide and a nickel composite hydroxide.
[0121] In addition, when the nickel-containing material contains a titanium compound, the form of the titanium compound is not particularly limited, and one or more selected from hydroxides, oxides, chlorides, nitrates, sulfates, carbonates, etc. may be used.
[0122] When the nickel-containing material contains a compound of element M, the form of the compound of element M is not particularly limited, and one or more selected from hydroxides, oxides, chlorides, nitrates, sulfates, carbonates, etc. may be used.
[0123] The nickel-containing material preferably contains nickel (Ni), titanium (Ti), and element M (M) in the following ratio. In terms of the molar ratio, Ni:Ti:M = b:c:e. Regarding b, c, e, and element M in the above formula, they may be the same appropriate ranges and materials as those described in "Regarding (1) Lithium Nickel Composite Oxide" and "Regarding (1-1) Composition" of the positive electrode active material, and thus the description is omitted here.
[0124] When the nickel-containing material is a nickel composite oxide, the nickel-containing material can be represented by, for example, the general formula: Ni b′ Ti c ′ M e ′ O 1+β is represented by.
[0125] When the nickel-containing material is nickel composite hydroxide, the nickel-containing material can be represented by, for example, the general formula: Ni b ′ Ti c ′ M e ′ (OH) 2+γ is represented by.
[0126] In addition, b′, c′, e′ and b, c, e above have the relationship of b′:c′:e′ = b:c:e, satisfying b′ + c′ + e′ = 1. The explanations about b, c, e and element M have been given, so the explanations are omitted here. β, γ are preferably, for example, -0.2 ≤ β ≤ 0.2, -0.2 ≤ γ ≤ 0.2.
[0127] When the nickel-containing material contains nickel composite hydroxide, there is no particular limitation on the manufacturing method of the nickel composite hydroxide, etc. For example, nickel composite hydroxide obtained by crystallization methods such as coprecipitation method and homogeneous precipitation method can be used.
[0128] In the mixing process, as part or all of the nickel-containing material, the above nickel composite hydroxide can be used as it is, or the nickel composite hydroxide can be oxidized and roasted and then used as the roasted product.
[0129] There is no particular limitation on the conditions for oxidizing and roasting the nickel composite hydroxide. Preferably, the above nickel composite hydroxide is oxidized and roasted in an oxidizing atmosphere at a temperature of 500 °C or higher and 800 °C or lower.
[0130] When using the roasted product of nickel composite hydroxide as the nickel composite compound, when sintering the first raw material mixture mixed with the lithium compound to obtain the lithium nickel composite oxide, the composition ratios of Li, Ni, Ti, and element M in the lithium nickel composite oxide can be made particularly stable.
[0131] There is no particular limitation on the atmosphere for oxidizing and roasting. As described above, it is preferably carried out in an oxidizing atmosphere, and more preferably carried out in an atmospheric atmosphere (air atmosphere), air flow that can be easily carried out.
[0132] (1-2) Lithium compound
[0133] The lithium compound is not particularly limited, and one or more selected from, for example, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium chloride, and lithium oxide can be preferably used. More preferably, one or more selected from lithium hydroxide and lithium carbonate can be used as the lithium compound. Lithium hydroxide has a high reactivity with the nickel composite compound and a low reaction temperature, and thus lithium hydroxide is further preferably used as the lithium compound.
[0134] Then, in the method for manufacturing the positive electrode active material of the present embodiment, as described above, the nickel-containing material and the lithium compound can be mixed to prepare the first raw material mixture.
[0135] The mixing ratio of the nickel-containing material and the lithium compound is not particularly limited, and the composition of lithium, nickel, and element M in the sintered product obtained after sintering basically maintains the composition in the first raw material mixture obtained by mixing the nickel-containing material and the lithium compound.
[0136] Here, when performing the subsequent water washing process or the like, lithium sometimes decreases slightly. Therefore, with respect to the total amount (Me) of, for example, nickel, titanium, and element M in the nickel-containing material, the amount of lithium (Li) in the lithium compound is preferably adjusted to be 1.005 or more and 1.100 or less in terms of the molar ratio (Li / Me).
[0137] By making the above Li / Me 1.005 or more, the crystallinity of the obtained lithium nickel composite oxide can be improved, and the content ratio of lithium in the obtained lithium nickel composite oxide relative to the elements other than oxygen can be the target composition.
[0138] In addition, by making the above Li / Me 1.100 or less, excessive sintering can be suppressed, for example, the sintering between secondary particles in the obtained lithium nickel composite oxide can be suppressed.
[0139] The device and method for mixing the nickel-containing material and the lithium compound are not particularly limited as long as the two can be uniformly mixed. For example, a dry mixer such as a V-type mixer or a mixing granulation device can be used.
[0140] (2) Sintering process
[0141] In the sintering process, the first raw material mixture can be sintered in an oxidizing atmosphere to obtain a sintered product. In the sintering process, when sintering the first raw material mixture, a sintered product in which lithium in the lithium compound diffuses and reacts in the nickel-containing material is obtained.
[0142] In the sintering process, the sintering temperature for sintering the first raw material mixture is not particularly limited, and can be, for example, 600 °C or higher and 1000 °C or lower.
[0143] By making the sintering temperature 600 °C or higher, the diffusion of lithium into the nickel-containing material can proceed sufficiently.
[0144] In addition, by setting the sintering temperature to 1000°C or lower, the sintering between the particles of the produced sintered material can be suppressed. In addition, the generation of abnormal grain growth can be suppressed, and the coarsening of the particles of the obtained sintered material can be suppressed.
[0145] During the process of heating up to the sintering temperature, it can be maintained for about 1 hour or more and 5 hours or less in the temperature range from near the melting point of the lithium compound used to the sintering temperature, for example, in the temperature range of 400°C or higher and 550°C or lower. By maintaining in the above temperature range, the reaction can proceed particularly uniformly.
[0146] The atmosphere during sintering is preferably an oxidizing atmosphere. There is no particular limitation for the oxidizing atmosphere, and an oxygen-containing gas atmosphere can be used. For example, an atmosphere with an oxygen concentration of 18% by volume or more and 100% by volume or less is more preferred.
[0147] This is because, by setting the oxygen concentration in the atmosphere during sintering to 18% by volume or more, the reaction between the lithium compound and the nickel-containing material can be promoted, and the crystallinity of the lithium nickel composite oxide can be improved.
[0148] When it is an oxygen-containing gas atmosphere, as the gas constituting the atmosphere, for example, air, oxygen, a mixed gas of oxygen and an inert gas, etc. can be used.
[0149] In addition, when using, for example, a mixed gas of oxygen and an inert gas as the gas constituting the oxygen-containing gas atmosphere, the oxygen concentration in the mixed gas preferably satisfies the above range.
[0150] In particular, the sintering step is preferably carried out in an oxygen-containing gas stream, more preferably in air or an oxygen stream. Considering the battery characteristics, it is further preferred that the sintering step is carried out in an oxygen stream.
[0151] In addition, there is no particular limitation for the furnace used for sintering, and it is only necessary to be able to sinter the first raw material mixture in a specified atmosphere. From the viewpoint of uniformly maintaining the atmosphere in the furnace, an electric furnace without gas generation is preferred, and both batch-type and continuous furnaces can be used.
[0152] In the method for manufacturing the positive electrode active material of the present embodiment, when the particles of the sintered material agglomerate during the sintering step, there can be a crushing step (the first crushing step) for crushing the sintered material.
[0153] Here, crushing refers to the following operation: mechanical energy is input to the aggregate composed of multiple secondary particles generated during sintering due to sintering necks between secondary particles, etc., and the secondary particles themselves are hardly damaged, and the secondary particles are separated to break the aggregate. For example, a needle mill, a hammer mill, a crusher, etc. can be used, and it is only necessary to crush to the extent that the secondary particles are not damaged.
[0154] In addition, the method for preparing the sintered product in the sintering process is not limited to the above method. For example, it can also be prepared by the following methods: a method of spray pyrolysis treatment of a liquid obtained by mixing all aqueous solutions containing the desired metal elements, a method of sintering after mechanically pulverizing and mixing all compounds of the desired elements by a ball mill, etc.
[0155] (3) Water washing process
[0156] In the water washing process, the sintered product obtained in the sintering process can be washed with water to obtain a washed powder. In the water washing process, the sintered product obtained in the sintering process and water can be mixed and washed as a slurry (slurry chemical process). The slurry concentration when washing the sintered product is not particularly limited. For example, it can be 200 g / L or more and 5000 g / L or less. By making the slurry concentration 5000 g / L or less, the stirring of the slurry can be facilitated, and the dissolution rate of the adhered substances can be increased.
[0157] On the other hand, by making the slurry concentration 200 g / L or more, the detachment of lithium from the lattice of the sintered product can be prevented, and the collapse of the crystal can be inhibited. In addition, by making the slurry concentration 5000 g / L or less, the re-precipitation of lithium carbonate caused by the absorption of carbon dioxide in the atmosphere by the high-pH aqueous solution can be prevented.
[0158] In addition, the water washing can be carried out as follows: controlling the temperature of the slurry in the temperature range of 10°C or more and 40°C or less, and making the conductivity of the liquid part of the slurry 30 mS / cm or more and 90 mS / cm or less.
[0159] By making the conductivity of the slurry prepared in the water washing process within the above range, the remaining components, such as remaining lithium, on the surface of the particles adhered to the sintered product can be selectively and sufficiently reduced.
[0160] The water used in the water washing process is not particularly limited. For example, water with a conductivity of less than 10 μS / cm, preferably 1 μS / cm or less, can be used.
[0161] There is no particular limitation on the water washing time. From the perspective of sufficiently removing the remaining components on the surface of the particles adhered to the sintered product and improving productivity at the same time, for example, it can be 3 minutes or more and 2 hours or less. In addition, it is preferable to stir the prepared slurry during the water washing period.
[0162] In the water washing process, after the slurry is liquefied, the slurry can be solid-liquid separated, that is, filtered and dehydrated, to obtain a washed powder (solid-liquid separation process). The filtration and dehydration are not particularly limited. For example, a pressure filter type solid-liquid separation device can be used.
[0163] In the water washing process, the water-containing washed powder obtained after solid-liquid separation is preferably dried and then provided to the boron addition process. Therefore, the washed powder can be dried (drying process). The drying conditions are not particularly limited.
[0164] The drying is preferably carried out at a temperature of 100 °C or higher and 250 °C or lower in, for example, an oxidizing atmosphere or a vacuum atmosphere. By setting the drying temperature at 100 °C or higher, the moisture in the water-washed powder can be sufficiently evaporated. In addition, by setting the drying temperature at 250 °C or lower, the energy required for drying can be suppressed, and the cost can be reduced.
[0165] In order to avoid the reaction of moisture and carbon dioxide in the atmosphere with the water-washed powder during drying, an atmosphere with suppressed or no water vapor and carbon dioxide is preferred. Specifically, an oxidizing atmosphere such as an oxygen atmosphere or a vacuum atmosphere is preferred. In addition, from the viewpoint of rapidly discharging the water vapor generated by drying, it is preferable to attach an exhaust mechanism to the drying device.
[0166] Regarding the drying time, there is no particular limitation, and it is preferably 0.5 hours or more and 48 hours or less, for example. By setting the drying time, that is, the holding time of the maximum temperature reached during drying, at 0.5 hours or more, the moisture in the water-washed powder can be sufficiently reduced and removed. In addition, by setting the drying time at 48 hours or less, the productivity can be improved.
[0167] (4) Boron addition step
[0168] In the boron addition step, the water-washed powder and the boron-containing material are mixed to prepare the second raw material mixture.
[0169] The boron-containing material to be added is not particularly limited. For example, it can be boron monomer or a boron-containing compound containing boron. That is, the boron-containing material is preferably at least one selected from boron monomer and boron-containing compounds. As the boron-containing compound, the components other than boron are preferably components that can be discharged out of the system in the subsequent heat treatment step. For example, orthoboric acid (H3BO3), boron oxide (B2O3), boron nitride (BN), etc. can be appropriately used, and the components other than B are compounds selected from one or more of hydrogen, oxygen, and nitrogen.
[0170] The mixing ratio of the water-washed powder and the boron-containing material is not particularly limited. In order to make the lithium nickel composite oxide obtained after heat treatment have the target composition, pre-tests, etc. are carried out, and the mixing ratio can be selected.
[0171] Here, generally, the composition in the lithium nickel composite oxide obtained after heat treatment will basically maintain the composition in the second raw material mixture. Therefore, it is preferable to prepare the second raw material mixture in such a way that the composition of the second raw material mixture is the same as the composition of the target lithium nickel composite oxide.
[0172] Here, in the subsequent heat treatment process, in order to make boron and the water-washed powder react uniformly, it is preferable to finely pulverize the added boron-containing material. Specifically, the average diameter in the long axis direction of the secondary particles of the boron-containing material observed in the surface SEM image is preferably 0.1 μm or more and 100 μm or less. The average diameter in the long axis direction is calculated as follows: arbitrarily extract 30 or more secondary particles of the boron-containing material observed with the surface SEM image, and take the average value of the particle diameters in the long axis direction measured for each secondary particle. In addition, the upper limit value of the number of secondary particles for measuring the particle diameter in the long axis direction is not particularly limited, and from the viewpoint of suppressing the time required for evaluation, it is preferably 100 or less.
[0173] The device and method for mixing the water-washed powder and the boron-containing material are not particularly limited as long as the two can be uniformly mixed. For example, a dry mixer such as a V-type mixer or a mixing granulation device can be used.
[0174] Here, in order to prevent the water-washed powder and the like from reacting with moisture and carbon dioxide in the atmosphere, the container during mixing is preferably purged with an inert gas. In addition, in order to suppress non-uniformity caused by aggregation of the boron-containing material, it is preferable to sieve the second raw material mixture several times after mixing the boron-containing material to break up the aggregation.
[0175] (5) Heat treatment process
[0176] In the heat treatment process, the second raw material mixture can be heat-treated.
[0177] It is considered that by implementing the heat treatment process, the formation of a lithium-boron-containing compound caused by the reaction between boron and the lithium component attached to the surface of the water-washed powder can be promoted.
[0178] In the heat treatment process, the heat treatment temperature for heat-treating the second raw material mixture is not particularly limited and can be selected according to the added boron-containing material and the like. In the heat treatment process, for example, it is preferably heat-treated at 200 °C or higher and 500 °C or lower, and more preferably heat-treated at 200 °C or higher and 400 °C or lower.
[0179] By making the heat treatment temperature 200 °C or higher, the reaction between the above-mentioned boron and lithium components can proceed sufficiently.
[0180] In addition, by making the heat treatment temperature 500 °C or lower, it is possible to prevent the boron and lithium components from flying in the atmosphere before the reaction.
[0181] The atmosphere during heat treatment in the heat treatment process is not particularly limited. For example, it can be carried out in an oxidizing atmosphere or an inert gas atmosphere.
[0182] As the oxidizing atmosphere, there is no particular limitation, and an oxygen-containing gas atmosphere can be used. For example, an atmosphere with an oxygen concentration of 18% by volume or more and 100% by volume or less is preferably used.
[0183] In the case of an oxygen-containing gas atmosphere, as the gas constituting the atmosphere, for example, air, oxygen, a mixed gas of oxygen and an inert gas, etc. can be used.
[0184] The heat treatment step is preferably carried out in an atmosphere in which the carbon dioxide concentration is suppressed, such as a decarbonized atmosphere. Therefore, preferably, for example, when it is the above-mentioned oxidizing atmosphere or inert gas atmosphere, the carbon dioxide concentration is also suppressed.
[0185] The carbon dioxide concentration in the heat treatment atmosphere is not particularly limited, and it is sufficient that the carbon dioxide concentration is lower than that in normal air. Therefore, the carbon dioxide concentration in the heat treatment atmosphere is preferably less than 0.03% by volume, more preferably 0.02% by volume or less, further preferably 0.01% by volume or less, and particularly preferably 0.008% by volume or less.
[0186] By carrying out the heat treatment in an atmosphere in which the carbon dioxide concentration is suppressed, the formation of carbon-containing compounds such as lithium carbonate can be suppressed, and thus the above-mentioned C content ratio can be suppressed, and the B content ratio relative to the C content ratio can be increased. After the heat treatment, it is preferable that the carbon dioxide concentration is also suppressed during cooling.
[0187] In addition, the furnace used for the heat treatment is not particularly limited, and it is sufficient to heat-treat the second raw material mixture in a specified atmosphere. From the viewpoint of uniformly maintaining the atmosphere in the furnace, an electric furnace without gas generation is preferable, and a batch-type or continuous-type furnace can be used.
[0188] In the method for manufacturing the positive electrode active material of the present embodiment, when agglomeration occurs in the particles of the lithium nickel composite oxide after the heat treatment step, a crushing step (second crushing step) for crushing the lithium nickel composite oxide may also be provided. Regarding the crushing, it can be carried out in the same manner as in the above-mentioned first crushing step, and thus the description is omitted.
[0189] [Lithium ion secondary battery]
[0190] The lithium ion secondary battery of the present embodiment (hereinafter also referred to as "secondary battery") includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the positive electrode may contain the positive electrode active material for the lithium ion secondary battery described above.
[0191] Hereinafter, regarding a configuration example of the secondary battery of the present embodiment, each structural element will be described separately. The secondary battery of the present embodiment, for example, contains a positive electrode, a negative electrode, and a non-aqueous electrolyte, and is composed of the same structural elements as a general lithium ion secondary battery. In addition, the embodiments described below are merely examples, and the lithium ion secondary battery of the present embodiment can be implemented in various modified and improved forms based on the knowledge of those skilled in the art starting from the following embodiments. In addition, the use of the secondary battery is not particularly limited.
[0192] (Positive electrode)
[0193] The positive electrode of the secondary battery according to this embodiment may contain the above-described positive electrode active material.
[0194] An example of the method for manufacturing the positive electrode will be described below. First, the above-described positive electrode active material (in powder form), conductive material, and binder (adhesive) may be mixed to form a positive electrode composite material. Further, a solvent for purposes such as adding activated carbon and adjusting viscosity may be added as needed, and the mixture may be kneaded to produce a positive electrode composite material slurry.
[0195] The mixing ratio of each material in the positive electrode composite material, since it is an element that determines the performance of the lithium-ion secondary battery, can be adjusted according to the application. The mixing ratio of the materials may be the same as that of the positive electrode of a known lithium-ion secondary battery. For example, when the total mass of the solid components of the positive electrode composite material excluding the solvent is 100% by mass, the positive electrode active material may be contained in an amount of 60% by mass or more and 95% by mass or less, the conductive material in an amount of 1% by mass or more and 20% by mass or less, and the binder in an amount of 1% by mass or more and 20% by mass or less.
[0196] The obtained positive electrode composite material slurry is coated on the surface of a current collector made of, for example, aluminum foil, dried to disperse the solvent, and a sheet-like positive electrode is produced. If necessary, in order to increase the electrode density, pressure may also be applied by roll pressing or the like. The sheet-like positive electrode thus obtained may be cut into an appropriate size according to the target battery and provided for the manufacture of the battery.
[0197] As the conductive material, for example, carbon black-based materials such as graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, and Ketjen black (registered trademark) may be used.
[0198] As the binder (adhesive), since it serves to connect and fix the active material particles, for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resins, and polyacrylic acid may be used.
[0199] As needed, the positive electrode active material, conductive material, etc. may be dispersed, and a solvent for dissolving the binder may also be added to the positive electrode composite material. Specifically, as the solvent, an organic solvent such as N-methyl-2-pyrrolidone may be used. In addition, in the positive electrode composite material, activated carbon may be added in order to increase the electric double layer capacitance.
[0200] The method for manufacturing the positive electrode is not limited to the above example, and other methods may also be used. For example, it may also be manufactured by pressing and molding the positive electrode composite material and then drying it in a vacuum atmosphere.
[0201] (Negative electrode)
[0202] The negative electrode can use metallic lithium, lithium alloys, etc. In addition, the negative electrode can be formed as follows: mix a negative electrode active material that can adsorb and desorb lithium ions with a binder, add an appropriate solvent to make it into a slurry state, coat the surface of a metal foil current collector such as copper with this negative electrode composite material, dry it, and compress it as needed to increase the electrode density.
[0203] As the negative electrode active material, for example, sintered bodies of organic compounds such as natural graphite, artificial graphite, and phenolic resin, and powder bodies of carbon materials such as coke can be used. At this time, as the negative electrode binder, similar to the positive electrode, fluorine-containing resins such as PVDF can be used, and as the solvent for dispersing these active materials and binders, organic solvents such as N-methyl-2-pyrrolidone can be used.
[0204] (Separator)
[0205] Between the positive electrode and the negative electrode, a separator can be interposed and arranged as needed. The separator separates the positive electrode and the negative electrode and holds the electrolyte. Well-known ones can be used, for example, films such as polyethylene and polypropylene, and membranes with a large number of micropores.
[0206] (Non-aqueous electrolyte)
[0207] As the non-aqueous electrolyte, for example, non-aqueous electrolytic solutions can be used.
[0208] As the non-aqueous electrolytic solution, for example, those obtained by dissolving a lithium salt as a supporting salt in an organic solvent can be used. In addition, ionic liquids in which a lithium salt is dissolved can be used as the non-aqueous electrolytic solution. In addition, an ionic liquid refers to a salt composed of cations and anions other than lithium ions and is in a liquid state at room temperature.
[0209] As the organic solvent, one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, and trifluoropropylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate, further, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane, sulfur compounds such as ethyl methyl sulfone and butane sultone, phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc. can be used alone, or two or more of them can be mixed and used.
[0210] As the supporting salt, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and their composite salts, etc. can be used. Further, the non-aqueous electrolytic solution can contain radical scavengers, surfactants, flame retardants, etc.
[0211] In addition, as the non-aqueous electrolyte, solid electrolytes can be used. Solid electrolytes have the property of being able to withstand high voltages. Examples of solid electrolytes include inorganic solid electrolytes and organic solid electrolytes.
[0212] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0213] There is no particular limitation on the oxide-based solid electrolyte. For example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electron insulation can be appropriately used. As the oxide-based solid electrolyte, for example, those selected from lithium phosphate (Li3PO4), Li3PO4N X , LiBO2N X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3 (0 ≤ X ≤ 1), Li 1+ X Al X Ge 2-X (PO4)3 (0 ≤ X ≤ 1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3 (0 ≤ X ≤ 2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 O4, etc., can be selected.
[0214] There is no particular limitation on the sulfide-based solid electrolyte. For example, a sulfide-based solid electrolyte containing sulfur (S) and having lithium ion conductivity and electron insulation can be appropriately used. As the sulfide-based solid electrolyte, for example, those selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc., can be used.
[0215] In addition, as the inorganic solid electrolyte, those other than the above can be used. For example, Li3N, LiI, Li3N-LiI-LiOH, etc., can be used.
[0216] As the organic solid electrolyte, there is no particular limitation on the polymer compound that exhibits ionic conductivity, and for example, polyethylene oxide, polypropylene oxide, their copolymers, etc. can be used. In addition, the organic solid electrolyte may contain a supporting salt (lithium salt).
[0217] (Shape and structure of the secondary battery)
[0218] The lithium-ion secondary battery of the present embodiment described above can have various shapes such as cylindrical and laminated. When adopting any of these shapes, when the non-aqueous electrolyte used in the present embodiment is a non-aqueous electrolyte solution, the structure can be as follows: the positive electrode and the negative electrode are laminated as an electrode body through a separator, the obtained electrode body is impregnated with the non-aqueous electrolyte solution, and between the positive electrode current collector and the positive terminal connected to the outside, and between the negative electrode current collector and the negative terminal connected to the outside, a current collecting lead or the like is used for connection, and it is sealed in a battery case.
[0219] In addition, as described above, the secondary battery of the present embodiment is not limited to the form of using a non-aqueous electrolyte solution as the non-aqueous electrolyte. For example, it can also be a secondary battery using a solid non-aqueous electrolyte, that is, an all-solid-state battery. When it is an all-solid-state battery, the components other than the positive electrode active material can be changed as needed.
[0220] The secondary battery of the present embodiment can be used for various purposes. Since the secondary battery of the present embodiment can be a high-capacity and high-output secondary battery, it is suitable as a power source for small portable electronic devices (such as laptop computers and mobile phone terminals) that often require high capacity, and is also suitable as a power source for electric vehicles that require high output.
[0221] In addition, since the secondary battery of the present embodiment can be miniaturized and have high output, it is suitable as a power source for electric vehicles with limited mounting space. In addition, not only as a power source for electric vehicles driven purely by electric energy, the secondary battery of the present embodiment can also be used as a power source for so-called hybrid vehicles that are used in combination with combustion mechanisms such as gasoline engines and diesel engines.
[0222]
Examples
[0223] Hereinafter, the present invention will be further described in detail by way of examples, and the present invention is not limited by any of these examples.
[0224] Here, first, the evaluation methods for the positive electrode active material and the secondary battery obtained in the following examples and comparative examples will be described.
[0225] (Evaluation of the positive electrode active material)
[0226] Regarding the obtained positive electrode active material, the following evaluations are carried out.
[0227] (a) Evaluation of composition, crystal structure, and particle structure
[0228] The composition analysis was performed using an ICP emission spectroscopic analyzer (manufactured by Shimadzu Corporation, ICPE-9000).
[0229] In addition, regarding the obtained positive electrode active material, the powder X-ray diffraction pattern was measured, and the crystal structure was determined by Rietveld refinement analysis. As a result, it was confirmed that the positive electrode active materials produced in the following Examples and Comparative Examples were composed of lithium nickel composite oxides, and the lithium nickel composite oxides had a hexagonal layered structure.
[0230] Furthermore, when observing the particles of the positive electrode active material using a scanning electron microscope, it was confirmed that the positive electrode active materials produced in the following Examples and Comparative Examples included secondary particles formed by aggregation of a plurality of primary particles.
[0231] (b) Proportion of B content, proportion of C content
[0232] Using an XPS apparatus (manufactured by Ulvac-phi, Versa Probe II), with the monochromatized Al-Kα line as the irradiation X-ray source, the photoelectron spectroscopy of the positive electrode active material was measured in a vacuum atmosphere of 1.0×10 -6 Pa or less.
[0233] Then, from the peak areas of the obtained photoelectron spectroscopy, the molar ratios of lithium, nickel, titanium, boron, element M, and carbon on the surface were calculated, and the proportion of B content, the proportion of C content, and the ratio of the proportion of B content to the proportion of C content were calculated by the above formulas (1) to (3). When calculating the molar ratios of the respective elements, after peak separation of the measured XPS photoelectron spectroscopy, for each element, the peak with the highest intensity was used.
[0234] (c) Peak intensity ratio
[0235] The XRD diffraction pattern of the positive electrode active material was measured using an XRD diffractometer (manufactured by PANalytical, X'Pert PRO) with Cu-Kα line as the radiation source. The measurement conditions were: output 45 kV, 40 mA, step size: 0.0168°, scanning speed: 0.0508° / sec.
[0236] From the obtained XRD pattern, the titanium compound contained in the positive electrode active material was determined by phase identification. The phase of the determined titanium compound is shown in the column of different phases in Table 1. In addition, except for Comparative Example 2, the phase of the titanium compound was not confirmed.
[0237] Next, the peak intensity of the strongest line with the maximum intensity among the peaks of each determined titanium compound was obtained. Then, the peak intensities of the strongest lines of the respective titanium compounds obtained were summed up to obtain the total peak intensity of the strongest lines of the titanium compounds.
[0238] In addition, from the obtained XRD pattern, the diffraction peak intensity of the (003) plane, which is the strongest line of the layered structure of the hexagonal system, was determined.
[0239] Then, the total amount of the peak intensities of the strongest lines of the above titanium compounds was divided by the diffraction peak intensity of the (003) plane, which is the strongest line of the layered structure of the hexagonal system, to obtain the peak intensity ratio (I Ti化合物 / I (003) ). In addition, in the column of "I Ti化合物 / I (003) " in Table 1, "-" indicates that the phase of the titanium compound was not confirmed in the XRD diffraction pattern, that is, the above peak intensity ratio was 0.
[0240] (d) Titration curve
[0241] 10 g of the positive electrode active material obtained in the following Examples and Comparative Examples was stirred in 50 mL of pure water for 5 minutes, and the filtered filtrate was neutralized and titrated with 1.0 M HCl to measure the titration curve. In addition, distilled water was used as the pure water.
[0242] From the obtained titration curve, the amount of HCl added in each pH region shown in the column of "HCl addition amount in neutralization titration" in Table 1 was determined. In addition, VR as the ratio of the HCl addition amounts was calculated by the above formula (4).
[0243] (e) Particle size distribution index
[0244] The volume-based particle size distribution was measured using a laser diffraction / scattering particle size distribution analyzer (MicrotracMT3300EXII, manufactured by Microtrac·BEL Co., Ltd.). D10, D90, and the volume average particle size Mv were calculated from the particle size distribution.
[0245] Then, [(D90 - D10) / volume average particle size Mv] as the particle size distribution index was calculated.
[0246] (Evaluation of battery characteristics)
[0247] (a) Reaction resistance
[0248] The button-type batteries fabricated in the following Examples and Comparative Examples were charged at a charging potential of 4.1 V, and the resistance was measured by the AC impedance method using a frequency response analyzer and a potentiostat-galvanostat (1255B, manufactured by Solartron). When the relationship between the measured structure and frequency was plotted, the Nyquist plot shown in Figure 2A was obtained.
[0249] The above Nyquist plot represents the sum of the characteristic curves of the solution resistance, the negative electrode resistance and its capacitance, and the positive electrode resistance and its capacitance. Therefore, as Figure 2B shown, an equivalent circuit based on this Nyquist plot is used to perform fitting calculations to calculate the value of the positive electrode resistance, and the calculated positive electrode resistance is used as the reaction resistance.
[0250] (b) Thermal stability
[0251] The thermal stability of the positive electrode active material is evaluated as follows. The positive electrode active material is made into an overcharged state and quantified by the amount of oxygen released by heating. The button-type batteries fabricated in the following Examples and Comparative Examples were CC charged at a rate of 0.05C (constant current-constant voltage charging) to a cut-off voltage of 4.3V. Then, the button-type battery was disassembled without short-circuiting, and only the positive electrode was carefully taken out, washed with DMC (dimethyl carbonate), and dried. About 2 mg of the dried positive electrode was taken, and using a gas chromatography mass spectrometer (GCMS, Shimadzu Corporation, QP-2010plus), it was heated from room temperature to 450°C at a heating rate of 10°C / min. Helium was used as the carrier gas. The generation behavior of oxygen (m / z = 32) generated during heating was measured, and the maximum oxygen generation peak intensity (peak height) obtained was determined.
[0252] Regarding the evaluation results in each of the Examples and Comparative Examples, with the maximum oxygen generation peak intensity in Comparative Example 1 as the reference, that is, 1.00, they are shown as relative ratios in the column of "Thermal stability" in Table 1. The smaller the value, the more the generation of oxygen is suppressed, and the better the thermal stability.
[0253] [Example 1]
[0254] (1) Fabrication of the positive electrode active material
[0255] (1-1) Mixing process
[0256] (Nickel-containing substance)
[0257] First, the following nickel composite oxide was prepared. The nickel composite hydroxide prepared by the neutralization crystallization method was subjected to oxidative calcination at a temperature of 600°C for 3 hours in an atmospheric atmosphere. In addition, the nickel composite oxide is a substance with a molar ratio of Ni:Mn:Co of 85:10:5, namely Ni 0.85 Mn 0.10 Co 0.05 O.
[0258] Then, the mixture of the above nickel composite oxide and TiO2 was used as the nickel-containing substance. The nickel composite oxide and TiO2 were mixed such that the molar ratio of Ni, Mn, Co, and Ti was Ni:Mn:Co:Ti = 0.829:0.098:0.049:0.024.
[0259] (Lithium compound)
[0260] As the lithium compound, lithium hydroxide is used. Further, as the lithium hydroxide, anhydrous lithium hydroxide is used.
[0261] Regarding the amount of substance of each element, the above nickel-containing material and lithium hydroxide were weighed and mixed in such a manner that Li / (Ni + Mn + Co + Ti) was 1.055 to obtain a first raw material mixture.
[0262] (1-2) Sintering process
[0263] The obtained first raw material mixture was heated to 840 °C in an oxygen atmosphere using an electric furnace, held at 840 °C for 2 hours, and sintered. Then, it was cooled to room temperature in the furnace. The obtained sintered product was subjected to a crushing treatment.
[0264] (1-3) Water washing process
[0265] Next, pure water at 20 °C was added to the obtained sintered product to form a slurry containing 1250 g of the sintered product per 1 L of water (slurry chemical process). After the slurry was stirred for 20 minutes, it was filtered under pressure to pass the liquid and dehydrated, whereby a washing filter cake containing water-washed powder (solid-liquid separation process) was produced. Further, as the pure water, water having a conductivity of 1 μS / cm or less was used.
[0266] The obtained washing filter cake was dried at 190 °C for 10 hours in a vacuum atmosphere to obtain water-washed powder (drying process).
[0267] (1-4) Boron addition process
[0268] The water-washed powder and orthoboric acid (H3BO3) as the boron-containing material were mixed to prepare a second raw material mixture. Here, 40 secondary particles of orthoboric acid arbitrarily extracted by observing the surface SEM image had an average diameter in the long axis direction of 3 μm.
[0269] The water-washed powder and orthoboric acid were put into a mixing container in such a manner that in the lithium nickel composite oxide obtained after the heat treatment process, the ratio of the amount of substance of the following elements was the ratio shown in Table 1, that is,
[0270] Li:Ni:Mn:Co:Ti:B = 1.03:0.825:0.097:0.049:0.024:0.005, and after the container was purged with N2 gas, they were mixed. After mixing, sieving was repeated 3 times to break up the aggregation of orthoboric acid.
[0271] (1-5) Heat treatment process
[0272] In the heat treatment process, the second raw material mixture is heat treated at 304 °C for 10 hours in an atmospheric atmosphere where carbon dioxide removal treatment is carried out. In addition, as the carbon dioxide-removed atmospheric atmosphere, air with a carbon dioxide concentration of 0.01% by volume or less after carbon dioxide removal treatment is used. After heat treatment at the above heat treatment temperature, it is cooled to room temperature in the atmosphere of the same carbon dioxide-removed atmosphere.
[0273] Regarding the lithium nickel composite oxide as the obtained positive electrode active material, the above evaluation is carried out. The evaluation results are shown in Table 1.
[0274] (2) Fabrication of secondary battery
[0275] A button-type battery with the structure as shown in Figure 1 is fabricated through the following procedure, and the above evaluation is carried out on this battery. The evaluation results are shown in Table 1.
[0276] As shown in Figure 1 , the button-type battery 10 is a lithium-ion secondary battery, which includes a positive electrode 11, a negative electrode 12, a separator 13, a gasket 14, a corrugated gasket 15, a positive electrode case 16, and a negative electrode case 17. In addition, the positive electrode 11, the negative electrode 12, and the separator 13 are impregnated with an electrolyte.
[0277] Inside the button-type battery 10, the positive electrode 11, the separator 13, the negative electrode 12, and the corrugated gasket 15 are laminated in sequence from the positive electrode case 16 toward the negative electrode case 17. The positive electrode 11 contacts the inner surface of the positive electrode case 16, and the negative electrode 12 contacts the inner surface of the negative electrode case 17 through the corrugated gasket 15.
[0278] The positive electrode case 16 and the negative electrode case 17 each have a hollow structure with one end open, and the negative electrode case 17 is disposed on the opening of the positive electrode case 16. The button-type battery 10 accommodates the positive electrode 11, the negative electrode 12, the separator 13, the gasket 14, and the corrugated gasket 15 between the positive electrode case 16 and the negative electrode case 17 by disposing the negative electrode case 17 on the opening of the positive electrode case 16.
[0279] In addition, the gasket 14 is disposed between the positive electrode case 16 and the negative electrode case 17. Through this gasket 14, the positive electrode case 16 and the negative electrode case 17 are restricted from relative movement and fixed in a non-contact state, that is, an electrically insulated state. In addition, the gasket 14 also has the function of sealing the gap between the positive electrode case 16 and the negative electrode case 17 and hermetically and liquid-tightly blocking between the inside and outside of the button-type battery 10.
[0280] The button-type battery 10 is fabricated as follows.
[0281] First, 52.5 mg of the prepared positive electrode active material, 15 mg of acetylene black, and 7.5 mg of polytetrafluoroethylene (PTFE) were mixed and pressed into a shape with a diameter of 11 mm and a thickness of 100 μm under a pressure of 100 MPa to produce the positive electrode 11 as shown in Figure 1 Then, the prepared positive electrode 11 was dried in a vacuum dryer at 120 °C for 12 hours.
[0282] After impregnating the positive electrode 11, the negative electrode 12, and the separator 13 with the electrolyte, a button-type battery 10 was fabricated inside a glove box with an Ar atmosphere where the dew point was managed at -80 °C. On the positive electrode case 16, the prepared positive electrode 11, separator 13, negative electrode 12, and corrugated gasket 15 were laminated in sequence. Next, the negative electrode 12 was brought into contact with the inner surface of the negative electrode case 17 via the corrugated gasket 15, and the negative electrode case 17 was covered on the opening of the positive electrode case 16, whereby the button-type battery 10 was assembled.
[0283] As the negative electrode 12, a disk-shaped negative electrode sheet material with a diameter of 14 mm was used. In this negative electrode sheet material, graphite powder with an average particle size of about 20 μm and polyvinylidene fluoride were coated on a copper foil.
[0284] As the separator 13, a polyethylene porous membrane with a film thickness of 25 μm was used.
[0285] As the electrolyte, the following was used: an equal-volume mixture (manufactured by Toyama Chemical Co., Ltd.) with a volume ratio of 1:1 of ethylene carbonate (EC) and diethyl carbonate (DEC) having 1 M of LiPF6 as a supporting electrolyte.
[0286] In addition, for the evaluation of the above reaction resistance and thermal stability, a total of 2 button-type batteries for each evaluation were fabricated under the same conditions.
[0287] [Examples 2 to 4]
[0288] In the boron addition process, the washed powder and orthoboric acid were mixed in the following manner so that the molar ratio of Li, Ni, Mn, Co, Ti, and B contained in the lithium nickel composite oxide obtained after the heat treatment process was the value shown in Table 1. Except for the above points, the positive electrode active material and the lithium ion secondary battery were manufactured under the same conditions as in Example 1 and evaluated. The evaluation results are shown in Table 1.
[0289] [Examples 5, 6]
[0290] In the heat treatment process, the heat treatment temperature was changed to the temperature shown in Table 1. Except for this point, the positive electrode active material and the lithium ion secondary battery were manufactured under the same conditions as in Example 2 and evaluated. The evaluation results are shown in Table 1.
[0291] [Comparative Example 1]
[0292] In the mixing process, TiO₂ is not added, and the boron addition process is not carried out after that. Except for this point, the positive electrode active material and the lithium-ion secondary battery are manufactured under the same conditions as in Example 1 and evaluated. That is, the washed powder obtained after the washing process is used as the positive electrode active material. The evaluation results are shown in Table 1.
[0293] [Comparative Example 2]
[0294] In the mixing process, the addition amount of TiO₂ is increased, and the mixture is made so that the molar ratio of Li, Ni, Mn, Co, and Ti contained in the lithium nickel composite oxide obtained after the washing process is the value shown in Table 1. In addition, the boron addition process is not carried out after that. That is, the washed powder obtained after the washing process is used as the positive electrode active material. Except for the above points, the positive electrode active material and the lithium-ion secondary battery are manufactured under the same conditions as in Example 1 and evaluated. The evaluation results are shown in Table 1.
[0295] [Comparative Example 3]
[0296] The heat treatment process is carried out in an air atmosphere without carbon dioxide removal treatment. That is, the carbon dioxide concentration in the air atmosphere is 0.03 vol% or more. Except for the above points, the positive electrode active material and the lithium-ion secondary battery are manufactured under the same conditions as in Example 2 and evaluated. The evaluation results are shown in Table 1.
[0297]
Table 1
[0298]
[0299] From the results shown in Table 1, it can be confirmed that the positive electrode active materials of Examples 1 to 6 contain boron in a specified ratio, the peak intensity ratio is 0.2 or less, and the ratio of the B content to the C content is 0.8 or more and 30.0 or less. And it was confirmed that when the positive electrode active materials of Examples 1 to 6 are used in a secondary battery, the reaction resistance can be reduced compared with the positive electrode active materials of Comparative Examples 1 to 3 that do not satisfy the above regulations.
[0300] It was also confirmed that when the positive electrode active materials of Examples 1 to 6 are used in a secondary battery, they are excellent in thermal stability compared with the positive electrode active material of Comparative Example 1.
[0301] This application claims the priority based on Japanese Patent Application No. 2022-175166 filed with the Japan Patent Office on October 31, 2022, and incorporates the entire contents of Japanese Patent Application No. 2022-175166 into this international application.
[0302]
Reference Signs
[0303] 10 Button-type battery (lithium-ion secondary battery)
[0304] 11 Positive electrode
[0305] 12 Negative electrode
[0306] 13 Separator
[0307] 14 Gasket
[0308] 15 Wave washer
[0309] 16 Positive electrode housing
[0310] 17 Negative electrode housing
Claims
1. A positive electrode active material for a lithium ion secondary battery, wherein, containing a lithium nickel composite oxide, the lithium nickel composite oxide having a layered structure of a hexagonal crystal system and comprising secondary particles formed by aggregation of a plurality of primary particles The lithium nickel composite oxide contains lithium (Li), nickel (Ni), titanium (Ti), boron (B) and an element M represented by M in the following proportions. In terms of the molar ratio, Li:Ni:Ti:B:M = a:b:c:d:e, where 0.95 ≤ a ≤ 1.10, 0.50 ≤ b < 1.00, 0.00 < c ≤ 0.05, 0.00 < d ≤ 0.03, 0.00 ≤ e ≤ 0.47, and b + c + d + e = 1. The element M is at least one element selected from the group consisting of Mn, Co, V, Mg, Mo, Ca, Cr, Zr, Ta, Nb, Na, W, Fe, Zn, Si, Sn, Cu, P and Al In the XRD pattern of the positive electrode active material for the lithium ion secondary battery, the ratio of the total peak intensity of the strongest lines of the titanium compound to the diffraction peak intensity of the (003) plane, which is the strongest line of the layered structure of the hexagonal crystal system, is 0.2 or less When the total amount of lithium, nickel, titanium, boron, the element M and carbon in the surface calculated from the XPS measurement results of the positive electrode active material for the lithium ion secondary battery is the total amount of substances, and the ratio of the amount of carbon to the total amount of substances is the C content ratio, and the ratio of the amount of boron to the total amount of substances is the B content ratio the ratio of the B content ratio to the C content ratio is 0.8 or more and 30.0 or less 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, by stirring 10 g of the positive electrode active material for a lithium ion secondary battery in 50 mL of pure water for 5 minutes, neutralizing and titrating the filtered filtrate with 1.0 M HCl, in the titration curve obtained thereby, the volume ratio of the amount of HCl added in the region where the pH is 5.0 or more and less than 8.0 to the amount of HCl added in the region where the pH is 8.0 or more and 11.0 or less is 0.5 or less.
3. The positive electrode active material for a lithium ion secondary battery according to claim 1 or 2, the C content ratio is 30% or less.
4. The positive electrode active material for a lithium ion secondary battery according to claim 1 or 2, calculated by the 90% diameter D90 based on volume in the particle size distribution, the 10% diameter D10 based on volume in the particle size distribution, and the volume average particle diameter Mv, [(D90 - D10) / Mv] representing the particle size distribution index is 0.70 or more and 1.20 or less, and the particle size distribution is based on the laser diffraction scattering method, the volume average particle diameter Mv is 8 μm or more and 20 μm or less.
5. A lithium ion secondary battery, at least including a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode includes the positive electrode active material for a lithium ion secondary battery according to claim 1 or 2.
Citation Information
Patent Citations
Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery using the same
JP2016189320A
Encryption system
JP2022175166A